(untitled) (World Bulletin of Public Health, 2024)
In the process of blood coagulation, initially under the influence of serotonin, the injured blood vessel shrinks and reduces the area of bleeding. Heparin is a direct-acting anticoagulant and has an anti-coagulant effect. Heparin on the surface of the endothelium keeps blood in a liquid state and prevents clotting factors from sticking to the surface of blood vessels.